Influence of the ankle joint dorsiflexion on the execution of vertical jumps - Papaiakovou, G.; Katsikas, F.; Nikodelis, T.; Panoutsakopoulos, V.; Kollias, T. (ISBS - Conference Proceedings Archive (Konstanz), 2006)
The purpose of the present study was to investigate the differences in the execution of vertical jumps between individuals with good and poor ankle dorsiflexion ability. Thirty (30) males and thirty (30) female P.E. students, after being evaluated for ankle dorsiflexion, formatted the flexible and inflexible groups (FG and IFG) and executed vertical jumps. In the SQJs the IFG exhibited more inclination of the trunk at the beginning of the jump, while in the CMJs and the DJs they applied greater forces and produced greater peak angular accelerations in all joints. The IFG, by leaning forward the trunk, underwent a greater injury risk for the low back while executing the SQJs. On the other hand, they underwent an increased injury risk for the achilles tendon by raising the heels off the ground and applying greater forces during the DJs.